AMG 151 (ARRY‐403), a novel glucokinase activator, decreases fasting and postprandial glycaemia in patients with type 2 diabetes. Issue 2 (14th December 2015) - Katz, L.; Manamley, N.; Snyder, W. J.; Dodds, M.; Agafonova, N.; Sierra‐Johnson, J.; Cruz, M.; Kaur, P.; Mudaliar, S.; Raskin, P.; Kewalramani, R.; Pellacani, A.
Abstract : Phase I studies have shown that AMG 151 activates glucokinase, a key enzyme in glucose homeostasis. The present randomized, placebo‐controlled phase IIa study evaluated the dose–effect relationship of the glucokinase activator AMG 151 relative to placebo on fasting plasma glucose (FPG) in 236 patients (33–35 patients per arm) with type 2 diabetes treated with metformin. Patients received oral AMG 151 at 50, 100 or 200 mg twice daily, AMG 151 at 100, 200 or 400 mg once daily or matching placebo for 28 days. A significant linear dose–effect trend was observed with the twice‐daily regimen (p = 0.004) for change in FPG to day 28. No trend was observed with the once‐daily regimen. A higher incidence of hypoglycaemia and hypertriglyceridaemia was observed with AMG 151 administration. AMG 151 significantly reduced FPG when administered twice daily but not when administered once daily in patients with type 2 diabetes treated with metformin.